THE STORY OF SLAUGHTERING COWS IN SURAH AL-BAQARAH - Nur Afiyah (Al'Adalah, 2022)
The name of surah al-Baqarah is taken from the story of slaughtering cows, verses 67 to 73. Suppose someone only reads the translation of the Qur'an or reads the Ijmali interpretation, of course. In that case, he will not be able to understand the story coherently because the verse arrangement is reversed. Therefore, it takes the narratological theory of the Qur'an to sequence the story so that it can be understood easily by historical chronology. The study uses a literature review by collecting the commentators, summarized in a book of commentaries. The study results are the story of the slaughter of a cow, starting from verses 72 and continuing with verses 67 to 71. After that, verse 72 is skipped and goes straight to verse 73. So, the chronological sequence of history is 72, 67, 68, 69, 70, 71, and 73. Based on it, al-Baqarah is a cow slaughtered by the Israelites to uncover the case of the murder of a nephew to his uncle. The nephew is the only heir. He could not wait for an inheritance, so he killed his wealthy uncle. He left the trail by placing the corpse in front of someone else's house at night. Then the case of finding the body went viral, and the Israelites accused each other of being confused about finding the culprit. After that, they asked Moses to solve the case; the order came down for the Israelites to slaughter a cow. Then, part of the cow was struck against the corpse, and he got up and said that the killer was his nephew.